Optical burst switching a new area in optical networking research. - Yang Chen (IEEE Network : the magazine of global information exchange)
In this tutorial, we give an introduction to optical burst switching and compare it with other existing optical switching paradigms. Basic burst assembly algorithms and their effect on assembled burst traffic characteristics are described first. Then a brief review of the early work on burst transmission is provided, followed by a description of a prevailing protocol for OBS networks called just-enough-time (JET). Algorithms used as an OBS core node for burst scheduling as well as contention resolution strategies are presented next. Trade-offs between their performance and implementation complexities are discussed. Recent work on QoS support, IP/WDM multicast, TCP performance in OBS networks, and labeled OBS is also described, and several open issues are mentioned.